Individual Preparedness and Response to Chemical, Radiological, Nuclear, and Biological Terrorist Attacks - Davis, Lynn E. (RAND Corporation, 2003)
Individuals may have to rely on themselves to protect their own health and safety--perhaps even their own lives--in the event of a terrorist attack. Even those who know how to take care of themselves in the event of a fire, tornado, or earthquake might not know what to do in case of a chemical, radiological, nuclear, or biological attack. This quick guide attempts to fill in some of these gaps by offering specific actions to take during each of these situations, as well as preparations that can be taken. These actions are appropriate regardless of the likelihood of an attack, its scale, or the current government alert level; are designed to be sensitive to potential variations; and have been defined in terms of simple rules that should be easy to follow. A reference card included at the back of the guide encapsulates the key points and can be removed for display in a prominent place.